redu termenii asemenea
2(x+y-xy)-3(xy-x-y)+(y-x-xy)
Răspunsuri la întrebare
Răspuns de
2
2(x+y-xy) - 3(xy-x-y) + (y-x-xy) =
2x+2y-2xy - (3xy-3x-3y) + y-x-xy =
2x+2y-2xy -3xy+3x+3y + y-x-xy =
2x +3x -x + 2y +3y +y -2xy -3xy -xy =
x(2+3-1) + y(2+3+1) - xy(2+3+1) =
x•4 + y•6 - xy•6 =
4x + 6y - 6xy
rebecapagu:
multumesc
Alte întrebări interesante
Ed. tehnologică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă